2017
DOI: 10.1039/c6nh00214e
|View full text |Cite
|
Sign up to set email alerts
|

Self-directing chiral information in solid–solid transformation: unusual chiral-transfer without racemization from amorphous silica to crystalline silicon

Abstract: Self-transfer of chiral information was found in the magnesiothermic reduction of amorphous chiral SiO2 nanofibers into crystalline Si.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 59 publications
0
34
0
Order By: Relevance
“…In our recent work, we found that chirality in silica is still retained even after bundles of chiral SiO 2 nanofibres were downscaled into sub‐10 nm SiO 2 nanoparticles. Optical activity manifested through stretching vibrations of Si−O bonds in vibrational circular dichroism (VCD) spectra . The chirality of our SiO 2 nanofibres should be accounted for by the asymmetric arrangement of Si and O atoms in Si−O clusters on the molecular scale .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our recent work, we found that chirality in silica is still retained even after bundles of chiral SiO 2 nanofibres were downscaled into sub‐10 nm SiO 2 nanoparticles. Optical activity manifested through stretching vibrations of Si−O bonds in vibrational circular dichroism (VCD) spectra . The chirality of our SiO 2 nanofibres should be accounted for by the asymmetric arrangement of Si and O atoms in Si−O clusters on the molecular scale .…”
Section: Methodsmentioning
confidence: 99%
“…Optical activity manifested through stretching vibrations of Si−O bonds in vibrational circular dichroism (VCD) spectra . The chirality of our SiO 2 nanofibres should be accounted for by the asymmetric arrangement of Si and O atoms in Si−O clusters on the molecular scale . Therefore, by trapping Eu 3+ (or Tb 3+ ) ions with the eventual formation of Eu 2 O 3 (or Tb 2 O 3 ) nanoparticles in chiral silica matrices, a local chiral environment on the size‐scale less than 10 nm is provided by the surrounding chiral clusters of Si−O linkages.…”
Section: Methodsmentioning
confidence: 99%
“…As described above, the chirality in silica is exactly based on irregular tetrahedra of SiO 4 throughout the silica network; thus, it would be a good candidate for transferring irregular tetrahedron structures to the reduced silicon. We performed the reduction of d ‐ and l ‐form silica pre‐sintered at 800 °C by Mg powders at 500–600 °C under an Ar atmosphere . The initial nanofibrous morphologies of the silica were completely destroyed after the reduction, whereas the silicon produced showed nanoflake morphology (Figure ).…”
Section: Chiral Silica's Potential As a Chiral Sourcementioning
confidence: 99%
“…We performed the reductiono fd-a nd l-form silica pre-sintered at 800 8Cb yM g powders at 500-600 8Cu nder an Ar atmosphere. [25] The initial nanofibrous morphologies of the silica were completely destroyed after the reduction, whereas the silicon produced showedn anoflake morphology ( Figure 13). As expected, the silicon flakes transformed from d-t ol-silica exhibited remarkable CD signals with am irror relationship in the absorption band of 400-500 nm (Figure 14).…”
Section: Enantiomerically Enriched Asymmetric Silica With Chiropticalmentioning
confidence: 99%
“…We recently revealed that cluster-like sub-10-nm chiral domains are present in our chiral silica. 22,23 In other words, the chirality would arise from the asymmetric arrangement of Si and O atoms through the nanofibrous silica frames (<10 nm). Although the detailed arrangement of Si and O atoms is still unclear, a certain number of SiO 4 tetrahedrons should arrange into molecular-scale helixes or the SiO 4 tetrahedrons are chirally distorted.…”
mentioning
confidence: 99%